Kinetic electromagnetic instabilities in an ITB plasma with weak magnetic shear. (2nd March 2018) - Chen, W.; Yu, D.L.; Ma, R.R.; Shi, P.W.; Li, Y.Y.; Shi, Z.B.; Du, H.R.; Ji, X.Q.; Jiang, M.; Yu, L.M.; Yuan, B.S.; Li, Y.G.; et al.
Abstract: Kinetic Alfvén and pressure gradient driven instabilities are very common in magnetized plasmas, both in space and the laboratory. These instabilities will be easily excited by energetic particles (EPs) and/or pressure gradients in present-day fusion and future burning plasmas. This will not only cause the loss and redistribution of the EPs, but also affect plasma confinement and transport. Alfvénic ion temperature gradient (AITG) instabilities with the frequency ω B A E < ω < ω T A E and the toroidal mode numbers n = 2 − 8 are found to be unstable in NBI internal transport barrier plasmas with weak shear and low pressure gradients, where ω B A E and ω T A E are the frequencies of the beta- and toroidicity-induced Alfvén eigenmodes, respectively. The measured results are consistent with the general fishbone-like dispersion relation and kinetic ballooning mode equation, and the modes become more unstable the smaller the magnetic shear is in low pressure gradient regions. The interaction between AITG activity and EPs also needs to be investigated with greater attention in fusion plasmas, such as ITER (Tomabechi and The ITER Team 1991 Nucl. Fusion 31 1135), since these fluctuations can be enhanced by weak magnetic shear and EPs.